(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: The eye changes associated with thyroid disease are referred to as Thyroid related Orbitopathy. A well described association exist between open angle glaucoma and thyroid related orbitopathy, the possible relationship between open angle glaucoma and either hypothyroidism or hyperthyroidism without orbitopathy is variable. Objective: To observe the relation of open angle glaucoma (OAG), glaucoma suspect (GS) and ocular hypertension(OHT) between Thyroid related immune orbitopathy (TRIO) and other thyroid diseases (toxic multinodular goiter and hypothyroidism). Method: With purposive type of sampling technique 40 patients of Graves’ disease disease in Group-A and 40 patients of other thyroid diseases in Group-B which was subdivided into 20 patients of toxic multinodular goiter in Group-B 1, 20 patients of hypothyroidism in Group-B2 were selected in Bangabandhu Sheikh Mujib Medical University (BSMMU) for this cross sectional study. The diagnosis of Graves’ disease, toxic multinodular goiter and hypothyroidism were carried out by history, clinical examination and clinical test in endocrinology department. All the patients underwent complete ocular examinations, measuring of intraocular pressure (IOP), fundus examination, visual field analysis, gonioscopy and exophthalmometry. Result: The OAG, GS and OHT was 7.5% (3 cases), 5.0% (2 cases) and 17.5% (7 cases) respectively in Group-A. In contrast OAG, GS was 5% (lease), 5% (1 case) respectively in Group-Bl, only 5% (1 case) OAG in Group-B2. There was no incidence of OHT in Group-B (B1+B2). Although the occurrence of OAG and GS were higher in Group-A than Group-B, this difference was not statistically significant (p>0.05). However OHT was more common in Group-A than Group-B and is statistically significant (p<0.05). Among the 12 patients with OAG, GS and OHT in Group-A, 11 had ?22mm exophthalmos. In Group-A, ?22mm exophthalmos in 60% cases, in contrast none of Group-B have ?22mm. Conclusion: The occurrence of OHT was higher in thyroid related immune orbitopathy than other thyroid diseases.